Trimeric Bet v 1-specific nanobodies cause strong suppression of IgE binding - Bauernfeind, Clarissa; Zettl, Ines; Ivanova, Tatiana; Goryainova, Oksana; Weijler, Anna Marianne; Pranz, Barbara; Drescher, Anja; Focke-Tejkl, Margarete; Pavkov-Keller, Tea; Eckl-Dorna, Julia; Tillib, Sergei V.; Flicker, Sabine (Frontiers in Immunology, 2024)
Around 20 % of the population in Northern and Central Europe is affected by birch pollen allergy, with the major birch pollen allergen Bet v 1 as the main elicitor of allergic reactions. Together with its cross-reactive allergens from related trees and foods, Bet v 1 causes an impaired quality of life. Hence, new treatment strategies were elaborated, demonstrating the effectiveness of blocking IgG antibodies on Bet v 1induced IgE-mediated reactions. A recent study provided evidence for the first time that Bet v 1-specific nanobodies reduce patients´ IgE binding to Bet v 1. In order to increase the potential to outcompete IgE recognition of Bet v 1 and to foster crossreactivity and cross-protection, we developed Bet v 1-specific nanobody trimers and evaluated their capacity to suppress polyclonal IgE binding to corresponding allergens and allergen-induced basophil degranulation. Nanobody trimers were engineered by adding isoleucine zippers, thus enabling trimeric formation. Trimers were analyzed for their cross-reactivity, binding kinetics to Bet v 1, and related allergens, and patients' IgE inhibition potential. Finally, their efficacy to prevent basophil degranulation was investigated. Nanobody Trimers showed enhanced recognition of cross-reactive allergens as well as and increased efficiency to reduce IgE-allergen binding compared to nanobody monomers. Furthermore, trimers displayed slow dissociation rates from allergens and suppressed allergen-induced mediator release. We generated highaffine nanobody trimers that target Bet v 1 and related allergens. Trimers and significantly blocked IgE-allergen interactions by competing with IgE for allergen binding. Trimers inhibited IgE-mediated triggered release of biological mediators, demonstrating a promising potential to prevent allergic reactions caused by Bet v 1 and its relatives.